2014
DOI: 10.4236/wjcd.2014.42008
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, diabetes mellitus, overweight and obesity in employees under health transition at the railways company in Congo-Brazzaville

Abstract: Background and Aim: Cardiovascular risk (CVR) factors, namely hypertension (HT), diabetes mellitus and obesity, are a public health problem in sub-Saharan Africa because of health transition. The additional effect of the social gradient within the railway companies in Congo-Brazzaville on high CVR is not yet established. The aim of this study was to determine the extent of hypertension, diabetes mellitus, overweight, and obesity and to identify the contributing factors of fatness and hypertension. Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Recent studies in Africa revealed that 23% of the urban population in Malawi, 35% in Niger, 55.6% in Ghana, and 38% in Kenya were obese [11]. Similarly, 65% of bank workers in Congo Brazzaville [12] and 86.8% of public and private organization workers in Nigeria were found to be obese [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in Africa revealed that 23% of the urban population in Malawi, 35% in Niger, 55.6% in Ghana, and 38% in Kenya were obese [11]. Similarly, 65% of bank workers in Congo Brazzaville [12] and 86.8% of public and private organization workers in Nigeria were found to be obese [13].…”
Section: Introductionmentioning
confidence: 99%